2017
DOI: 10.1177/2156587217717414
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antimicrobial Activities of the Essential Oil From Salvia mirzayanii Leaves

Abstract: Resistance of many pathogens to available drugs is a global challenge and is leading to growing interest in natural alternative products. In this study, chemical composition and in vitro antibacterial and antifungal activities of the essential oil from Salvia mirzayanii were investigated. The chemical constituents of essential oil from S mirzayanii were analyzed by gas chromatography–mass spectrometry. The antimicrobial activity was determined by broth microdilution. The main identified compounds were 1,8-cine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 29 publications
(58 reference statements)
0
8
0
Order By: Relevance
“…The results from the measurement of MIC and MBC, followed by the growth curve indicated that linalool had strong and consistent inhibiting effects on P. fluorescens ( Figure 1 ). EOs (from Litsea cubeba leaf, Salvia mirzayanii, Zataria multiflora, Gnaphlium affine, Forsythia koreana ) affect the structure of the cell envelope because it was found that the major antibacterial compositions of the EOs could penetrate through the cell wall and destroy the cytoplasmic membrane ( Zeng et al, 2011 ; Kavoosi and Rabiei, 2015 ; Yang et al, 2015 ; Zomorodian et al, 2017 ; Nguyen et al, 2018 ). Scanning electron microscope (SEM) results showed that the cell morphology changed after linalool treatment ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results from the measurement of MIC and MBC, followed by the growth curve indicated that linalool had strong and consistent inhibiting effects on P. fluorescens ( Figure 1 ). EOs (from Litsea cubeba leaf, Salvia mirzayanii, Zataria multiflora, Gnaphlium affine, Forsythia koreana ) affect the structure of the cell envelope because it was found that the major antibacterial compositions of the EOs could penetrate through the cell wall and destroy the cytoplasmic membrane ( Zeng et al, 2011 ; Kavoosi and Rabiei, 2015 ; Yang et al, 2015 ; Zomorodian et al, 2017 ; Nguyen et al, 2018 ). Scanning electron microscope (SEM) results showed that the cell morphology changed after linalool treatment ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The initial column temperature was 60°C for 2 min. Then raised to 250°C at 2/min and held for 5 min (Zomorodian, Moein, Pakshir, Karami, & Sabahi, 2017).…”
Section: Gas Chromatography-mass Spectrometry Analysismentioning
confidence: 99%
“…Many studies have documented EOs to be effective antimicrobial agents against several pathogens [14][15][16]. Usually, this EO effect is closely related to the capability of permeabilizing and/or destroying membrane integrity, leading to the leakage of intracellular substances [17][18][19]. Moreover, since the last decade, the antibiofilm activity of EOs has been widely explored and reported in the literature [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%